Tafsir and Local Interpretation Analysis:: Study of Muqatha’ah Letters in the Qur'an through the Perspective of K.H. Bisri Mustofa - Dwi Nugraha, Arnawan (Institut Agama Islam Persis Bandung, 2024)
This article discusses the interpretation of K.H. Bisri Mustofa regarding the Muqatha’ah letters in the Qur'an. The localization of Javanese-language tafsir books and the nuances of Nusantara interpretation underscore the significance of studying this topic. This study uses a quantitative study method with a literature review approach. The data sources are the book